ANALISIS KEANEKARAGAMAN MAKROFITA AKUATIK DAN MAKROZOOBENTOS SEBAGAI BIOINDIKATOR KUALITAS AIR DI SUNGAI JANGKOK TERKAIT AKTIVITAS PEMUKIMAN DI KOTA MATARAM: Analysis of Aquatic Macrophyte and Macrozoobenthos Diversity as Bioindicators of Water Quality in the Jangkok River in Relation to Residential Activities in Mataram City - Nufus, Chairun; Tarmizi, Azhari (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2026)
Jangkok River is one of the main rivers in Mataram City, whose entire course is strongly influenced by residential activities. This study aimed to analyze the diversity of aquatic macrophytes and macrozoobenthos as bioindicators of water quality. The research was conducted using a survey method at several observation stations. Aquatic macrophyte samples were collected using the quadrat method, while macrozoobenthos were collected using a standardized laboratory sieve. Physicochemical parameters measured included temperature, pH, dissolved oxygen, salinity, water color, and substrate type. Data analysis was performed using the Shannon–Wiener diversity index, evenness index, and dominance index. The results indicated that a total of 33 aquatic macrophyte species and 11 macrozoobenthos species were identified. Based on ecological indices, the water quality of the Jangkok River was classified as slightly to moderately polluted